Optimasi Pelarut Pengembang dalam Pemisahan Benzil Asetat dari Ekstrak Bunga Tanaman Melati - Rinaningsih Rinaningsih (Universitas Negeri Surabaya, 2012)
Jasmine plant flower (Jasminum sambac) have a range of benefits. The compounds of these plants which are useful for medicine are benzyl acetate, acetic acid and indole linalil. The objective of this research was to identify the best developer solvent. Solvents used to identify the developer who is benzene, chloroform, benzene - chloroform (1:1), benzene - ethyl acetate (19:1). Based on the amount of stain on TLC chromatograms and spectral similarity as determined by TLC - Densitometer brand Simatsu type CS - 930, the most appropriate developer solvent to identify the benzyl acetate from the extract of jasmine is chloroform (CHCl3). This is partly because the price matches or see imminent standard polarity of benzyl acetate with chloroform as a developer solvent is better than another developer solvents and mixed solvents other developers. [Index polarity of benzyl acetate = 4.3, benzene = 0, chloroform = 4.4, benzene-chloroform (1:1) = 2.2, benzene - ethyl acetate (19:1) = 0.215]. Hence, it can be concluded that the best developer solvent or mix developers solvent to separate the benzyl acetate from the extract of Jasmine is the developer solvent chloroform.